(untitled) (Research, Society and Development, 2021)
Introduction: Cardiac arrest is responsible for a high rate of morbidity and mortality, even in situations of ideal care. Its definition consists of the interruption of effective respiratory and circulatory activities, and its intervention consists of applying a series of emergency procedures in order to reestablish oxygenation and circulation. Objectives: To analyze the nurse’s assistance during a cardiac arrest in the Mobile Emergency Care Service. Methods: This is an integrative review of literature of the exploratory type with a quantitative approach, considering the materials available in the BVS and LILACS databases. Results: According to the research, two divisions were generated for presentation of the evidence and discussion of the theme. In the first, they are presented: Assistance of the professional nurse in the care of the victim in CRA in the Mobile Emergency Care Service. The second division presents: Determinant factors of immediate survival after cardiopulmonary resuscitation maneuvers in out-of-hospital cardiac arrest. Conclusion: It was observed that there is still a lack of knowledge about the protocol before a CRA by the professional nurse, focused on the importance of CPR maneuvers with efficiency, since the nurse is mostly the first to arrive at the scene.